A fuzzy model for evaluating the level of tourist movement to infrastructure and accessibility in the regions - Gavurova, Beata; Polishchuk, Volodymyr; Polishchuk, Inna (Transformations In Business & Economics, 2026)
The issue of forecasting demand and researching its dimensions, including tourism infrastructure, has not yet been sufficiently explored. From the available studies, it can be concluded that the traditional theories of demand in tourism and the various model approaches are applied for its investigation. Therefore, a sufficient space is created for the improvement of techniques, approaches, methods, and tools that enable obtaining new outcomes for the decision-making processes and for the construction of policies. The main goal of this study was to develop a fuzzy model for evaluating the level of tourist movement to infrastructure and accessibility in the regions of the V4 countries, based on travel satisfaction relative to the expected and actual experience of participants in the tourist movement. For the first time, a model of fuzzy logical inference of level of travel satisfaction relative to expected and actual experience from infrastructure and accessibility is developed. The research results were tested, and the developed model was verified on real data from 2,343 participants of the tourist movement for the regions of the V4 countries. The effective policies and the efficient decision-making processes are one of the most important ways to eliminate the regional disparities and discrepancies impacting the economic, health, social, and environmental fields of each country.